A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 5 years ago
How do you: Use f(x) = 3x 5 and g(x) = 2  x^2 to evaluate the following expressions:
1. (a) f(g(0)) (b) g(f(0))
2. (a) (f ` g) (2) (b) g(g(3))
anonymous
 5 years ago
How do you: Use f(x) = 3x 5 and g(x) = 2  x^2 to evaluate the following expressions: 1. (a) f(g(0)) (b) g(f(0)) 2. (a) (f ` g) (2) (b) g(g(3))

This Question is Closed

campbell_st
 5 years ago
Best ResponseYou've already chosen the best response.1find g(0)... by substituting x = 0 into g(x)... then substitute that answer into f(x0 1. (a) f(g(0)) g(0) = 2 f(2) = 3 x 2  5 = 1 (b) similar to (a) but start with f(0) 2. (a) looks like finding the derivative of f(x) = 3 not sure on the notation (b) find g(3)... then substitute that answer into g(x) again
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.